النشاط السياسي للنقابات المغاربية خلال الفترة الإستعمارية _الجزائروالمغرب الأقصى أنموذجا - هناء صيد; ليلى بوقرحة (جامعة الوادي - University of Eloued, 2025)
"تناولت هذه الدراسة موضوع النشاط السياسي للنقابات المغاربية خلال الفترة الاستعمارية -الجزائر والمغرب أنموذجا، حيث تمحورت إشكالية البحث في كيف ساهمت النقابات العمالية في كل من الجزائر و المغرب خلال الفترة الإستعمارية في الحركة السياسية و في ما تمثلت هذه الإسهامات، وفي هذا السياق قسمنا الموضوع الى: مقدمة و ثلاث فصول وخـاتمـة. اما عن الفصل الأول فقد ابرزنا الظروف التي سبقت ظهور الحركة النقابية المغاربية والذي تضمن بوادر ظهور الحركة النقابية المغاربية ثم نشأة وتطور الحركة النقابية المغاربية وأيضا النقابات المغاربية المستقلة، اما عن الفصل الثاني مخصص لدراسة النشاط السياسي للنقابات المغاربة المستقلة في اوله تضمنت النشاط السياسي للإتحاد العام للعمال الجزائريين، ثم النشاط السياسي للإتحاد المغربي للشغل، اما في الفـصل الثالث فتناولنا فيه دراسة مقارنة بين التجربتين المغربية والجزائرية والذي تضمن أوجه الاختلاف و أوجه التشابه. أخيرا خاتمـة إحتوت مجمــوعة نتائج التي تم التوصل اليها و هي ان ظهور النضال العمالي داخل كل من الجزائر والمغرب، لم يأتي من العبث بل كان عبارة عن نتيجة للقمع و الإستغلال الذي فرضه الإستعمار الفرنسي على كل من الجانب الإقتصادي والإجتماعي وسياسة التمييز التي كانت دائما حاضرة بين العمال المغاربة "This study addressed the topic of the political activity of Maghreb unions during the colonial period, with Algeria and Morocco as a model. The research problem revolved around how labor unions in both Algeria and Morocco contributed to the political movement during the colonial period and what these contributions represented. In this context, we divided the topic into an introduction, three chapters, and a conclusion. As for the first chapter, we highlighted the circumstances that preceded the emergence of the Maghreb union movement, which included the beginnings of the emergence of the Maghreb union movement, then the emergence and development of the Maghreb union movement, as well as the independent Maghreb unions. As for the second chapter, it is devoted to studying the political activity of independent Moroccan unions. It initially included the political activity of the General Union of Algerian Workers, followed by the political activity of the Moroccan Labor Union. As for the third chapter, we dealt with a comparative study between the Moroccan and Algerian experiences, which included aspects of difference and similarityFinally, a conclusion containing a set of results that were reached, which is that the emergence of the workers' struggle within both Algeria and Morocco did not come out of nowhere, but was rather a result of the oppression and exploitation imposed by French colonialism on both the economic and social aspects, discrimination, and the policy of discrimination that was always present among Moroccan workers. Keywords: political activity, labor unions, trade union movement "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: الحركة النقابية; النقابات العمـالية; النشاط السياسي; Political activity - labor unions - trade union movement